Co‐inhibitory profile and cytotoxicity of CD57+PD‐1– T cells in end‐stage renal disease patients. (9th November 2017) - Kraaijeveld, R.; de Graav, G. N.; Dieterich, M.; Litjens, N. H. R.; Hesselink, D. A.; Baan, C. C.
Summary: Blockade of the CD80/86‐CD28 pathway by belatacept after kidney transplantation is associated with an increased risk of rejection compared with standard, calcineurin inhibitor (CNI)‐based therapy. CD28 – T cells, which express CD57, are not susceptible to belatacept treatment. High numbers of CD4 + CD57 + programmed death 1 (PD‐1) – T cells pretransplantation have been associated with a higher chance of rejection, although conflicting data have been reported. To investigate the working mechanism behind this possible higher chance of rejection, we studied the expression of co‐inhibitory molecules (CD223, CD244 and PD‐1), proliferative capacity and cytotoxic potential of fluorescence activated cell sorted (FACS) CD4 + CD57 + PD‐1 – and CD8 + CD57 + PD‐1 – T cells, and their CD57 – control populations, after alloantigen stimulation. The effect of belatacept on the cytotoxic capacity of pretransplantation peripheral blood mononuclear cells from 20 patients who received belatacept post‐transplantation was also tested. Expression of co‐inhibitory molecule CD223 increased by approximately 10‐fold after allogeneic stimulation in all four T cell subsets. Proliferation and up‐regulation of CD244 and PD‐1 was observed for CD4 + CD57 ‐ PD‐1 – T cells after allogeneic stimulation, but no up‐regulation of these markers occurred on CD8 + T cells or CD4 + CD57 + PD‐1 – T cells. However, CD4 + CD57 + PD‐1 – T cells and, to a lesser extent, CD8 + CD57 + PD‐1 – T cells displayed higher cytotoxicity as indicated by granzyme B expression. Belatacept inhibited the cytotoxic potential of CD4 + CD57 + PD‐1 – T cells (median of inhibition 31%, P  < 0·01) and CD8 + CD57 + PD‐1 – T cells (median of inhibition 10%, P  < 0·05). In conclusion, alloantigen‐activated CD4 + CD57 + PD‐1 – T cells exhibited a less proliferative but more cytotoxic profile than their CD57 – counterparts. Their cytotoxic capacity can be inhibited partly by belatacept and was not associated with development of rejection after kidney transplantation. Abstract : We show that CD4 + CD57 + PD‐1 ‐ T cells show a more senescent, but a potentially more cytotoxic profile than their CD57 ‐ counterpart. This cytotoxic potential can be partly inhibited by belatacept in both groups and this inhibition was not associated with the development of rejection after kidney transplantation.